Experimental psychology and visual artwork: Notes from the laboratory - Vogt, Stine (FormAkademisk, 2018)
This article explores ways in which modern experimental psychology can provide information about aspects of the processes involved in the creation of visual art. Many areas of research in the fields of neuroscience and cognitive neuropsychology yield information that can be used to develop techniques to benefit the production of art. Several phenomena are discussed to provide a comprehensive perspective on the psychological, behavioural and physiological processes that influence the creation of artwork. Keywords: paradoxical facilitation, cognitive psychology, system 1, system 2, verbal overshadowing, perceptual constancy, categorical, coordinate, TMS